SINTESIS DAN UJI TOKSISITAS SENYAWA 1-(2,4-DIKLOROFENIL)-3-(3,4-DIMETOKSIFENIL)PROPENON - Husnul Khatimah; Agung Rahmadani; M. Arifuddin; Rolan Rusli (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Chalcone has been widely reported to have various activities such as cytotoxic, antioxidant, antibacterial, and others. Synthesis becames the right way to get chalcone because it can produce much yield of chalcone and can be varied in accordance with the desired structure. The compound of 1-(2,4-dichlorophenyl)-3-(3,4-dimethoxyphenyl)propenone was synthesized by conventional method for 6 hours using a 40% NaOH catalyst with a yield of 90.87%. The toxicity test of 1-(2,4-dichlorophenyl)-3-(3,4-dimethoxyphenyl)propanone was done by Brine Shrimp Lethality Test method (BSLT). The results of the test showed that the 1-(2,4-dichlorophenyl)-3- (3,4-dimethoxyphenyl)propenone has toxicity value LC50 613.05 ppm.